2013
DOI: 10.1037/a0032794
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability: How students’ responses to uncertainty and novelty predict their academic and non-academic outcomes.

Abstract: Adaptability is defined as appropriate cognitive, behavioral, and/or affective adjustment in the face of uncertainty and novelty. Building on prior measurement work demonstrating the psychometric properties of an adaptability construct, the present study investigates dispositional predictors (personality, implicit theories) of adaptability, and the role of adaptability in predicting academic (motivation, engagement, disengagement) and non-academic (self-esteem, life satisfaction, sense of meaning and purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
330
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 249 publications
(374 citation statements)
references
References 82 publications
29
330
1
2
Order By: Relevance
“…These results clearly support the importance of personality constructs in substantive educational research (e.g. Martin, Nejad, Colmar, & Liem, 2013;Martin, Papworth, Ginns, & Liem, 2014), particularly with regard to adaptive and maladaptive forms of motivation .…”
Section: Modelsupporting
confidence: 64%
“…These results clearly support the importance of personality constructs in substantive educational research (e.g. Martin, Nejad, Colmar, & Liem, 2013;Martin, Papworth, Ginns, & Liem, 2014), particularly with regard to adaptive and maladaptive forms of motivation .…”
Section: Modelsupporting
confidence: 64%
“…Relevant to the focus of our study, past research has indicated that students who favored incremental over entity beliefs have higher grades (Romero, Master, Paunesku, Dweck, & Gross, 2014), endorse more learning goals (Blackwell, Trzesniewski, & Dweck, 2007), use better reading strategies (Braasch, Braten, Stromso, & Anmarkrud, 2014), and practice more (Cury, Da Fonseca, Zahn, & Elliot, 2008). Conversely, entity beliefs have been linked with decreases in intrinsic motivation (Haimovitz, Wormington, & Corpus, 2011) and academic disengagement (Martin, Nejad, Colmar, & Liem, 2013).…”
Section: Implicit Ability Beliefsmentioning
confidence: 90%
“…Recently, the concept of adaptability has been introduced and found to explain significant variance in academic and non-academic wellbeing, beyond the effects of factors such as buoyancy and selfregulation (Martin et al, 2013). The American Psychological Association (APA) defined adaptability as "the capacity to make appropriate responses to changed or changing situations; the ability to modify or adjust one's behavior in meeting different circumstances or different people" (VandenBos, 2007, p. 17).…”
Section: Adaptabilitymentioning
confidence: 99%